Comparing peripherally inserted central catheter-related practices across hospitals with different insertion models: a multisite qualitative study. Issue 8 (24th December 2020) - Krein, Sarah L; Harrod, Molly; Weston, Lauren E; Garlick, Brittani R; Quinn, Martha; Fletcher, Kathlyn E; Chopra, Vineet
Abstract : Background: Peripherally inserted central catheters (PICCs) provide reliable intravenous access for delivery of parenteral therapy. Yet, little is known about PICC care practices or how they vary across hospitals. We compared PICC-related processes across hospitals with different insertion delivery models. Methods: We used a descriptive qualitative methodology and a naturalist philosophy, with site visits to conduct semistructured interviews completed between August 2018 and January 2019. Study sites included five Veterans Affairs Medical Centres, two with vascular access teams (VATs), two with PICC insertion primarily by interventional radiology (IR) and one without on-site PICC insertion capability. Interview participants were healthcare personnel (n=56), including physicians, bedside and vascular access nurses, and IR clinicians. Data collection focused on four PICC domains: use and decision-making process, insertion, in-hospital management and patient discharge education. We used rapid analysis and a summary matrix to compare practices across sites within each domain. Results: Our findings highlight the benefits of dedicated VATs across all PICC-related process domains, including implementation of criteria to guide PICC placement decisions, timely PICC insertion, more robust management practices and well-defined patient discharge education. We also found areas with potential for improvement, such as clinician awareness of PICC appropriateness criteria and alternative devices, deployment of VATs and patient discharge education. Conclusion: Vascular access nurses play critical roles in all aspects of PICC-related care. There is variation in PICC decision-making, care and maintenance, and patient education across hospitals. Quality and safety improvement opportunities to reduce this variation are highlighted.